QUALITY OF LIFE OF ELDERLY PATIENTS WITH OSTEOARTHRITIS - Ibadova Olga Alexandrovna, Gulandom Zikriyevna Shodikulova, Ergashova Madina Muxtorovna (Journals Park Publishing, 2023)
BMD) on the quality of life (QOL) of patients over 65 years of age with various clinical forms of osteoarthritis (OA).Material and methods. 93 patients over 65 years of age with a diagnosis of OA corresponding to the criteria of R. Altman were examined. Anthropometric indicators, duration of the disease, degree of functional insufficiency were evaluated in all patients, X-ray examination of joints, densitometry were performed. According to the results of densitometry, the patients were divided into two groups. The main group consisted of 69 patients with osteopenic syndrome, the control group consisted of 24 examined with normal MPKT. In each of the groups, patients with the main clinical forms of OA (according to the most affected joint) were identified: gonarthrosis, oligoarthrosis, polyosteoarthrosis. General (SF-36) and special (WOMAC index) questionnaires were used to assess the quality of life.The results of the study. According to the results of the SF-36 questionnaire, a decrease in BMD in patients with OA worsens all indicators of QOL, especially the psychological component of health. An increase in the number of affected joints is characterized by a deterioration in QOL. The presence of osteopenic syndrome in elderly patients with OA significantly reduces QOL according to the WOMAC index scales, which characterize the severity of pain in the joints and the functional ability of patients, while the dependence on the clinical forms of OA has not been traced.
Keywords: bone mineral density, osteoarthritis, osteoporosis, old age, quality of life.